Model stenskega uparjanja za popis podhlanejega vrenja toka pri nizkih tlakih - Končar, Boštjan (Strojniški vestnik, 2005)
In this paper we propose a wall-evaporation model for sub-cooled flow boiling under low pressures. The model is based on local mechanisms of bubble nucleation and captures the effect of the developing thermal boundary layer near the heated wall. The model was incorporated into the one-dimensional thermal-hydraulic code RELAP5. The modified code was validated against a number of published low-pressure sub-cooled boiling experiments (1 to 4), and in contrast to the existing code it shows good agreement with the experimental data.
Keywords: stensko uparjanje; vrenje; modeli